Minimally invasive lumbar decompression in an ambulatory surgery center - Patel, Dil V. (J Spine Surg, 2019)
BACKGROUND: There is limited data regarding clinical and surgical outcomes of minimally invasive lumbar decompression (MIS LD) as an outpatient procedure. In this context, our purpose is to evaluate a single surgeon’s experience with performing MIS LD in the outpatient versus inpatient setting and determining if there are differences in surgical and clinical outcomes. METHODS: Patients undergoing primary, one- to three-level MIS LD were retrospectively reviewed and stratified by surgical setting: ambulatory surgical center (ASC) versus hospital. The cohorts were compared with respect to demographics, perioperative characteristics, complications, postoperative pain and narcotics consumption, and improvements in patient-reported outcomes. RESULTS: Five hundred and nine patients were included: 332 patients underwent surgery at an ASC and 177 patients underwent surgery at a hospital. The ASC patients were younger, more likely to be male, and carry Workers’ Compensation insurance. The hospital patients were older, more likely to be diabetic, and had a greater comorbidity burden. Patients undergoing MIS LD in an ASC were less likely to have multi-level procedures and more likely to have decompression with discectomy compared to patients in the hospital cohort. There were two cases of superficial wound infection in the ASC cohort and a single case of a pulmonary embolus in the hospital cohort. Additionally, a total of 28 patients had recurrent herniated nucleus pulposus in the ASC cohort compared to 12 patients in the hospital cohort. There was one case of residual stenosis in the ASC cohort compared to eight cases in the hospital cohort. Both cohorts demonstrated similar preoperative ODI, VAS back pain, and VAS leg pain scores through 12-month follow-up. CONCLUSIONS: MIS LD is a safe and effective procedure in an ASC, however, appropriate patient selection and postoperative protocols are imperative in minimizing complications and optimizing safety and efficacy in the outpatient setting.